ANALISIS PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP KEPERCAYAAN DAN CITRA MEREK SERTA DAMPAKNYA TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Lazada.co.id di Semarang) - Yulianto, Muhammad Rizal; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2020)
This research aims to analyze the influence of Electronic Word of Mouth on Trust and Brand Image and the impact on Purchasing Decision on Lazada.co.id e-commerce platform. At this time, E-commerce has become common thing in community. Technological developments and convenience obtained make this platform has growing demand in all market segments. From ease of use to the speed of e-commerce services into the spotlight of consumers.This research was conducted for people in Semarang City who had carried out buying and selling transactions through the Lazada.co.id platform. The number of samples is 100 respondent. With the method of collecting data through questionnaires and sampling methods in this study is a non probability sampling with purposive sampling technique. Analysis method with AMOS program. The results show that Electronic Word of Mouth has a positive and significant effect on Trust and Brand Image. Then, Trust and Brand Image has a positive and significant effect on purchasing decision.